Investigation on Friction Stir Weldability Characteristics of AA7075-T651 and AA6061-T6 Based Nanocomposites. (21st December 2021) - Madhusudan, M.; Shanmuganatan, S. P.; Shridhar, Kurse; John, Jacob; Krishnamurthy, R.; Sasikumar, Bashyam
Abstract : Friction stir welding (FSW) is an emerging solid-state process and alternative to fusion welding, wherein frictional heat is generated between a nonconsumable rotating steel tool and the work substrate. The present study focuses on the influence of the operating attributes like tool pin contact geometry, welding speed, and tool rotational speed on dissimilar aluminum matrix nanocomposites. AA6061-T6 and AA7075-T651 aluminum alloy plates were joined via double-pass FSW with the inclusion of 5 vol. % of nanoscale h-BN particles. Welding was performed with four rotational speeds (600, 800, 900, and 1000 rpm), three traversing speeds (30, 40, and 60 mm/min), and three distinct tool pin geometry (cylindrical, threaded cylindrical, and square), respectively. Besides, unreinforced and reinforced weldments were analyzed for mechanical properties like tensile strength and microhardness. Microstructural characterization was also carried out using FESEM and XRD techniques. The findings concluded that the reinforced samples welded using a cylindrical tool and double-pass strategy showcased homogenous distribution of nanoparticles with grain refinement, thereby exhibiting improved strength and hardness.